Etika Komunikasi Dakwah dalam Perspektif Naqd Al-Naṣṣ: Analisis Tafsir Kontemporer Ali Al-Harb terhadap QS. An-Nahl: 125 - Amirulloh; Abdurrahman, Haris; Nazirah, Annida; Samiah, Siti Robiah; Kurniawan, Muhammad Rizki; Andi Rosa (Prodi Komunikasi Penyiaran Islam Sekolah Tinggi Agama Islam As-Sunnah, 2025)
Abstract This study examines the ethical concept of Islamic communication in the contemporary interpretation of Ali al-Harb toward QS. An-Nahl [16]:125. The main problem addressed in this study is the decline of ethical and dialogical values in modern da'wah communication, especially in digital media. Using a qualitative library research method with a hermeneutical and contemporary tafsir approach, this research explores how Ali al-Harb’s Naqd al-Nash (textual critique) provides a new understanding of the Qur’an that is reflective, critical, and contextual. The findings reveal that the principles of bil hikmah, mau‘izhah hasanah, and mujādalah billatī hiya ahsan form the foundation of Qur’anic-based communication ethics. These three principles construct a model of da'wah ethics that integrates intellectual, emotional, and moral dimensions, allowing da'wah practices to become more humanistic, moderate, and adaptive to the digital era. The study concludes that Ali al-Harb’s hermeneutical interpretation offers a relevant framework for developing ethical standards in contemporary Islamic communication.